2014
DOI: 10.1089/cyber.2014.0302
|View full text |Cite
|
Sign up to set email alerts
|

Is Online Better Than Offline for Meeting Partners? Depends: Are You Looking to Marry or to Date?

Abstract: Previous studies that compared differences in the outcomes of relationships that begin online compared to traditional offline venues have primarily looked at marital relationships. The present study extends this investigation by including non-marital relationships in the comparison. It further investigates if the breakup rate of relationships (both marital and non-marital) varies as a result of meeting online versus offline, and if other factors outside of the meeting venue predict relationship dissolution. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 10 publications
1
22
0
1
Order By: Relevance
“…Heterosexual couples who met online transitioned to marriage faster than heterosexual couples who met offline. My results overturn earlier results (Paul 2014) that claimed that HCMST data showed that couples who met online had higher rates of breakup.…”
Section: Discussionsupporting
confidence: 85%
“…Heterosexual couples who met online transitioned to marriage faster than heterosexual couples who met offline. My results overturn earlier results (Paul 2014) that claimed that HCMST data showed that couples who met online had higher rates of breakup.…”
Section: Discussionsupporting
confidence: 85%
“…A total of eleven studies were found that examined the characteristics of use or motivations of online dating use. Out of the eleven studies, there were ten quantitative studies, all of which were cross-sectional (Corriero and Tong 2016;Gunter 2008;Hance et al 2018;Houran and Lange 2004;Hwang 2013;Kim et al 2009;Menkin et al 2015;Paul 2014;Stinson and Jeske 2016;Valkenburg and Peter 2007), and one qualitative study (Lawson and Leck 2006). One study examined heterosexual respondents only (Hwang 2013), and another study focused on male homosexual populations only (Corriero and Tong 2016), and the remaining studies did not differentiate between sexual orientations.…”
Section: Usage and Motivationsmentioning
confidence: 99%
“…B. Sex oder Dates) zu präferieren (Clemens et al 2015;Hall et al 2010) und sexuelle Abenteuer zu suchen (Schmitz et al 2011;Owen et al 2011;Paul 2014;Martins et al 2015;Sumter et al 2017). Frauen hingegen nutzen Online-Dating-Plattformen häufiger, um längerfristige Beziehungen (z.…”
Section: Typische Nutzer_innengruppenunclassified